MENJAWAB PROBLEMATIKA KONTEMPORER (Kajian terhadap Pemikiran Maslahah Mursalah al-Ghazali) - Kholis, Nur (Islamic University of Indonesia, 2003)
The article below traces how Islamic law anticipates occurring of contemporer problematics according to Ghazaliâs Maslahah Mursalah thought. According al-Ghazali, Maslahah Mursalah can be made as an argument for Islamic law determining if it fulfils many requirements: maslahat is suitable with syaraâ, maslahat is not contrary with al-Qurâan, as-Sunnah, and ijma, and maslahat is existing in daruriyat level or hajiyat that in same level with daruriyat. Maslahah mursalah is not independent dalil that stand alone from al-Qurâan, asSunnah, and Ijmaâ, but it is one of Islamic law istimbat methode. In other word, maslahah mursalah is not resource of Islamic law but methode of Islamic law discovering. Assembling of maslahah mursalah as dalil for Islamic law determining, it makes many moslems contemporer problematics can be known and determined although their law status not mentioned in al-Qurâan and as-Sunnah. So, maslahah mursalah assembling makes Islamic law always appropriate whenever and wherever.